2013
DOI: 10.1016/j.jmoldx.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of EGFR Signaling Pathway Somatic DNA Mutations Derived From Peripheral Blood and Corresponding Tumor Tissue of Patients with Advanced Non-Small-Cell Lung Cancer Using Liquidchip Technology

Abstract: Somatic DNA mutations affecting the epidermal growth factor receptor (EGFR) signaling pathway are known to predict responsiveness to EGFR-tyrosine kinase inhibitor drugs in patients with advanced non-small-cell lung cancers. We evaluated a sensitive liquidchip platform for detecting EGFR, KRAS (alias Ki-ras), proto-oncogene B-Raf, and phosphatidylinositol 3-kinase CA mutations in plasma samples, which were highly correlated with matched tumor tissues from 86 patients with advanced non-small-cell lung cancers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…As shown in Figure 1, after primary screening, 34 full-text articles10131415162223242526272829303132333435363738394041424344454647484950 were selected for further evaluation of eligibility. By rigorous evaluation, 20 eligible studies were identified and included in meta-analysis1314151622232425262728293031323334353637.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1, after primary screening, 34 full-text articles10131415162223242526272829303132333435363738394041424344454647484950 were selected for further evaluation of eligibility. By rigorous evaluation, 20 eligible studies were identified and included in meta-analysis1314151622232425262728293031323334353637.…”
Section: Resultsmentioning
confidence: 99%
“…Circulating free DNA (cfDNA) has been proposed as an alternative approach for the detection of EGFR mutation1112. Numerous studies have investigated the diagnostic performance of cfDNA and a wide range of the concordance rates between cfDNA and tissues have been reported13141516.…”
mentioning
confidence: 99%
“…Limitations exist on the uncertainty of collection methods and diversity of phenotypes of CTCs in blood (8). And detecting circulating tumor DNA in plasma requires molecular methods such as polymerase chain reaction-based technology (9,10), high-performance liquid chromatography (11), and mutant-enriched liquid chips (12), which are complicated, technique dependent, and time consuming. The ideal method should be noninvasive, be readily available, need minimal or no sample preparation, and provide immediate information on EGFR mutation status, which is important for the long-term management of patients with NSCLC to enable clinicians to adjust therapeutic strategies, improving the outcome of targeted therapy.…”
mentioning
confidence: 99%
“…Indeed, ctDNA can be a potential source of tumor DNA alteration pursuing for the documentation of tumor-associated genetic changes in order to real-time tumor monitoring [4,53,78,79]. For NonSmall Cell Lung Cancer Research (NSCLC), numerous clinical centers have investigated the diagnostic precision of ctDNA for EGFR mutation detection [80][81][82][83]. In 2016 the U.S. Food and Drug Administration (FDA) agreed to the EGFR Mutation Test v2, a blood-based companion diagnostic for the cancer drug Tarceva (Erlotinib) [84].…”
Section: Lung Cancermentioning
confidence: 99%